A Comparative Study of 0.25% Levobupivacaine, 0.25% Ropivacaine, and 0.25% Bupivacaine in Paediatric Single Shot Caudal Block. (31st October 2018) - Sharma, Jagdeep; Gupta, Ruchi; Kumari, Anita; Mahajan, Lakshmi; Singh, Jasveer
Abstract : Aim . There are limited data comparing levobupivacaine, ropivacaine, and bupivacaine in paediatric patients. So, this study was performed to evaluate the caudal effectiveness of all the three drugs in paediatric patients undergoing infraumbilical surgeries and associated complications with these drugs. Material and Methods . 90 patients of ASA grade I and II posted for elective infraumbilical surgeries were randomly divided into three groups of 30 each. A standardized anaesthetic protocol was used. Patients received 0.25% levobupivacaine in group 1, 0.25% ropivacaine in group 2, and 0.25% bupivacaine in group 3. The effectiveness of block was assessed using caudal effectiveness score. Postoperative pain relief was assessed with modified Hannallah pain score. Haemodynamic parameter monitoring was done. The duration of analgesia and associated complications were studied. Statistical analysis was done using the chi-square test for nonparametric data. Parametric data were analysed using ANOVA for intergroup comparison and Tukey's HSD for intragroup comparison. Results . Demographic data were comparable. Haemodynamic parameters remained within normal range. Mean caudal effectiveness score in all the three groups was statistically insignificant (p > 0.05 ). The duration of analgesia provided by bupivacaine (145.31 ± 26.17 min) was longer than levobupivacaine (126.15 ± 15.15 min) and ropivacaine (114.68 ± 11.32 min) (p < 0.01 ). Mean postoperative pain scores were lower in group 3 as compared to group 1 and group 2. Conclusion . We conclude that levobupivacaine and ropivacaine provide similar intraoperative quality with minimal haemodynamic variability and shorter duration of postoperative analgesia without any significant complications when compared with racemic bupivacaine. This trial is registered withCTRI/2018/03/012402 .